Faktor-Faktor yang Mempengaruhi Opini Audit, Kesulitan Keuangan, Biaya Profesional dan Ukuran Perusahaan Klien Terhadap Pergantian Audit dalam Industri Properti dan Real Estat - Monica Fortunata; Susanto (Economic Reviews Journal, 2024)
Auditor Switching is expected to enhance the quality of auditor independence, thereby ensuring that audit outcomes are free from subjectivity. Previous research analyzing factors influencing Auditor Switching has yielded various results, prompting a need for reexamination. This study is designed to analyze the relationships between Audit Opinion, Financial Distress, Professional Services, Client Company Size and Auditor Switching within the Property and Real Estate Industry. The relationships among variables are explained using agency theory. The study employs quantitative data sourced from the real estate industry, specifically annual reports filed with the Indonesia Stock Exchange between 2019 and 2023, as well as official company websites. Purposive sampling method was utilized to select 185 samples from the population. Based on logistic regression analysis conducted using SPSS version 27, it can be concluded that Audit Opinion effect significantly positive to Auditor Switching, whereas Financial Distress, Professional Fees and Client Company Size do not influence Auditor Switching.